The potential of slimpac as a management information system sofiware - an overview - Mohd. Yunus, Mohd. Zulkifli (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1997)
The selection of GIS software applications vary with the purposes and requirements of using it. The two major applications for GIS software are for management/information and design analysis. The surveyors Land Information Management PACkage (SLIM) is basically developed for management or monitoring purposes and some design applications. Studies on areas of applications. specifications, operations. data sources, data organisations and information presentation shows the potentials of SLIMPAC as a Management Information System Package.